THE TOLERANCE AND YIELD COMPONENTS OF RICE BREEDING LINES SELECTED UNDER LOW AND OPTIMUM NITROGEN CONDITIONS - Angelita Puji Lestari; Suwarno Suwarno; Trikoesoemaningtyas Trikoesoemaningtyas; Didy Sopandie; Hajrial Aswidinnoor (Indonesian Journal of Agricultural Science, 2019)
One of the important issues on rice breeding is to develop new rice lines suitable for nitrogen efficiency in the suboptimum environment. The study aimed to evaluate the tolerance and yield components of rice breeding lines selected under low and high nitrogen conditions. The F6 generation from two cross-combinations of Gampai/IR77674 and Progol/Asahan, were evaluated in the dry season of 2014 under N suboptimum and N optimum conditions. A total of 172 lines plus six check varieties derived from the low and high N environment selection were evaluated under low N rate (34.5 kg N ha-1) and high N rate (138 kg N ha-1), arranged in an augmented design. Six check varieties were relocated three times in each block. Plot size was 5.5 m2 and plant spacing 20 cm x 20 cm. Data were collected for grain yield and major yield components. Results showed that the different status of nitrogen fertilizer affected the number of productive fillers, number of filled grains, 100-grain weight, and grain yield. Different cross combinations exhibited different results in the progeny performance. Ten lines have a higher yield also tolerant to low N condition, i.e. B14250F-6-9, B14250F-1-4, B14250F-9-9, B14250F-6-4, B14250F-5-2, B14262F-15-6, B14250F-2-6, B14262F-12-4, B14250F-5-1, and B14250F-11-4. Thus, to obtain the N tolerant lines, selection at a low N environment was more effective compared with the optimum selection environment.